Vitamin B12 and Folate Markers Are Associated with Insulin Resistance During the Third Trimester of Pregnancy in South Asian Women, Living in the United Kingdom, with Gestational Diabetes and Normal Glucose Tolerance. Issue 1 (9th November 2021) - Sobczyńska-Malefora, Agata; Yajnik, Chittaranjan S; Harrington, Dominic J; Hitman, Graham A; Finer, Sarah
ABSTRACT: Background: Gestational diabetes mellitus (GDM) can adversely affect the health of the developing fetus. Women of South Asian origin are particularly at risk of developing GDM. Insulin resistance (IR) contributes to the etiology of GDM, and although studies have shown associations of vitamin B12 (B12 ) and folate status with GDM and IR, only a limited number of B12 and folate markers have been used. Objective: We used a comprehensive panel of B12 and folate markers to examine their association with IR in pregnant women with diet-controlled GDM and normal glucose tolerance (NGT). Methods: In this cross-sectional study, 59 British-Bangladeshi women (24 GDM and 35 NGT) with a mean age of 29 y, BMI (in kg/m 2 ) 26.7 and gestational age 33 wk were recruited. Serum total B12, holotranscobalamin, folate, methylmalonic acid, plasma homocysteine, 5-methyltetrahydrofolate, and red cell folate (RCF) were measured along with other parameters. The independent sample t -test and chi-squared test were used to assess differences in markers between GDM and NGT women. Spearman's test was used to look for correlations. A simple multiple regression analysis was used to investigate if markers of B12 and folate status predicted IR, using the HOMA-IR and adjusting for age, GDM status, and BMI. Results: There were no differences in concentrations of B12 and folate markers between GDM and NGT women. In Spearman's analysis HOMA-IR correlated negatively with total serum B12 ( P < 0.001) and holotranscobalamin ( P < 0.05), and positively with BMI ( P < 0.001), blood pressure ( P < 0.05) and triglycerides ( P < 0.05) in all women. MMA did not correlate with any of the B12 markers. In regression analysis, total B12 ( β = −0.622, P = 0.004), RCF ( β = 0.387, P = 0.018), and BMI ( β = 0.024, P < 0.001) were the significant predictors of HOMA-IR variance. Conclusions: Significant associations between markers of B12 and folate status with HOMA-IR were found during the third trimester in British-Bangladeshi women. B12 markers correlated poorly with each other.